Optimizing Educational Delivery: Cloud-Based Solutions for Effective Distance Learning - Ahmad, Asiyah (PT. Lentera Ilmu Publisher, 2023)
This paper explores the transformative role of cloud-based technology in revolutionizing distance education, emphasizing its pivotal significance in a rapidly evolving educational landscape. Amid global challenges and technological advancements, particularly in cloud computing, the paper underscores the critical role cloud technology plays in optimizing learning material delivery and fostering interactions within the educational sphere, especially in the context of distance learning. Through an in-depth analysis, this study investigates the adoption and optimization of cloud-based technology by educational institutions to surmount accessibility barriers, elevate learning quality, and offer more interactive and inclusive learning experiences. By evaluating the adaptability of cloud-based solutions, the paper highlights their potential not only in facilitating learning but also in stimulating innovation within the education sector. Moreover, the research delves into essential elements such as security, infrastructure, and technical support necessary for successful cloud technology implementation in educational environments. As a foundational exploration, this study provides valuable insights and guidance, laying the groundwork for further research aimed at achieving more effective and inclusive education in the digital era.